Flood risk area assessment in Patong Municipality, Kathu District, Phuket Province, Thailand - S Vongtanaboon; W Hancharoen; S Homya (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2019)
The objectives of this research were to evaluate risk factors and assess flood risk areas, including analyzing guidelines for flood risk area management in Patong Municipality, Kathu District, Phuket Province. Factors affecting flood were rainfall, slope gradient, soil permeability, land use, and water barrier. Weighting factors and rating factors were indicated and geographic information system for potential surface analysis and overlay analysis were applied. The results revealed that Patong Municipality had high risk area as 2.17 km2 (11.39%). Flood risk area for moderate level accounted for 4.00 km2 (20.99%) and low flood risk area accounted for 12.89 km2 (67.62%). Guidelines for flood risk area management in Patong Municipality should focus on the principles of soil and water conservation, forest restoration and preservation in the upstream area, flow path and stream are management, land use management, ground cover planting to prevent soil erosion and maintain soil moisture.